Production of second generation ethanol using Eucalyptus dunnii bark residues and ionic liquid pretreatment. (October 2016) - Reina, Luis; Botto, Emiliana; Mantero, Carlos; Moyna, Patrick; Menéndez, Pilar
Abstract: The production of ethanol using Eucalyptus dunnii bark pretreated with 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) as ionic liquid (IL) was studied. In the present work high ethanol yields were obtained using the minimal quantity of IL necessary for wetting but not dissolving the lignocellulosic material. The best result obtained was 70% of ethanol yield using an IL:bark ratio of 5:1, with separate hydrolysis and fermentation (SHF) process, and a cellulase load of 50 FPU/gram of pretreated material. Highlights: Eucalyptus dunnii bark was surveyed relative to lignocellulosic ethanol production. Ionic liquid ([BMIM]Cl) was used in the pretreatment step. High load of bark relative to ionic liquid was studied (5:1, ionic liquid:bark ratio). A high yield of ethanol using ionic liquid pretreatment of bark was obtained. A 70% of ethanol yield was obtained in a Separate Hydrolysis and Fermentation process.